DYNAMIC PHYSICAL-GEOLOGICAL MODEL OF THE FIELD OF DIAMONDS FROM THE KOMSOMOLSKAYA KIMBERLITE PIPE (ALAKIT-MARKHA FIELD OF WESTERN YAKUTIA) - K. M. Konstantinov; A. S. Gladkov (Геодинамика и тектонофизика)
Petrophysical, tectonophysical and paleomagnetic studies were done on the field of diamonds from the Komsomolskaya kimberlite pipe to interpret the observed gravimagnetic field. As a result of studying the structural-material complexes (SMC) of the field, there was formed a dynamic physical-geological model (DPhGM). The structure of the deposit is a dynamically developing network of faults that control heterochronous igneous complexes (kimberlites and traps). The features of the tectonic structure and physical properties of the SMC of the field were reflected in the nature of the observed gravitational and magnetic fields. DPhGM provides proofs for the existence of geophysical anomalies, genetically related to the structures of diatreme association – anomalies of the structural type.